Cataract Surgery Cancellations: An Analysis of Financial and Resident Training Implications at a Major Eye Institution - Padidam, Sneha; Wisner, Douglas; Kenney, Brianna; Peterson, Jared; Pizzi, Laura; Leiby, Benjamin E.; Hark, Lisa; Bailey, Robert; the Wills Cataract Research Group (Journal of Academic Ophthalmology, 2018)
Purpose The objective of this study was to assess reasons for cancellation of resident-performed cataract surgery, identify modifiable barriers to completion of the surgery on the scheduled date, and analyze the healthcare reimbursements and educational experiences lost as a result of cancellations.Setting General eye clinic staffed by residents in a major urban center.Design Retrospective, observational study.Methods The study compared patients (older than 18 years) who canceled their cataract surgery to patients who underwent surgery on their scheduled date. Cancellation and reimbursement information was obtained from the surgical coordinator's scheduling book and billing information. Demographic information was obtained from patient electronic medical records, and scheduling logs. A brief phone survey was implemented to identify patient's barriers to surgery if a reason for cancellation was undocumented.Results The overall cancellation rate over 1-year was 29.54% and most common overall reason for cancellation was that preadmission testing (PAT) was not completed in time for the procedure. Overall, 72% of the cancellations were made within 7 days of the surgery. The total estimated lost potential reimbursement due to cancellation was $844,370. The relative loss of surgical opportunities for residents throughout this 1-year period was 230 cases or 29 surgeries per resident.Conclusion These findings have prompted a new study testing whether on-site mandatory PATs conducted on the same day as the patient's ophthalmology evaluation will reduce cataract surgery cancellation rates.
Keywords: cataract surgery cancellation; cataract surgery; resident training; reimbursement information; preadmission testing; cancellation rate; surgical opportunities